2014
DOI: 10.7161/anajas.2014.29.3.231-239
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT LEVELS OF NITROGEN AND PHOSPHORUS ON THE YIELD AND YIELD COMPONENT OF FALSE FLAX (Camelina sativa L.) CRANTZ)

Abstract: vejetasyon dönemlerinde Ankara ekolojik koşullarında yürütülmüştür. Deneme Tesadüf Bloklarında Bölünen Parseller Deneme Deseni'ne göre üç tekerrürlü olarak kurulmuştur. Denemede ana parsellere fosfor dozları (0, 3, 6, 9 kg/da), alt parsellere de azot dozları (0, 5, 10, 15, 20 kg/da) uygulanmıştır. Bu çalışmanın amacı; ketencik (Camelina sativa (L.) Crantz) bitkisinde farklı fosfor ve azot dozlarının bitki boyu (cm), yan dal sayısı (adet/bitki), 1000 tohum ağırlığı (g), dekara tohum verimi (kg/da), yağ oranı (%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
2
5
1
Order By: Relevance
“…Results showed that the most thousand seeds weight (1.04 g) was recorded at 7-10 April using 80 kg ha -1 phosphorus. It was observed before that effects of phosphorus doses on thousand seeds weight (1.28-1.31 g) in camelina were significant which are in contrast with our results (Arslan et al, 2014). Also, in another study, it was showed that different sowing times had significant effects on thousand seeds weight (0.22-0.62 g) (Katar et al, 2012a).…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Results showed that the most thousand seeds weight (1.04 g) was recorded at 7-10 April using 80 kg ha -1 phosphorus. It was observed before that effects of phosphorus doses on thousand seeds weight (1.28-1.31 g) in camelina were significant which are in contrast with our results (Arslan et al, 2014). Also, in another study, it was showed that different sowing times had significant effects on thousand seeds weight (0.22-0.62 g) (Katar et al, 2012a).…”
Section: Discussioncontrasting
confidence: 97%
“…40 and 80 kg ha -1 P 2 O 5 applications were at the same groups. Arslan et al (2014) showed that the highest number of branches (8.9) obtained by using 60 kg ha -1 P fertilizer while the least number (6.4) recorded in control plots. It was reported that number of branches were 8.28-12.43 at different sowing times (Katar et al, 2012b) which is compatible with the results of present study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations